Shock experiments on basalt—Ferric sulfate mixes and their possible relevance to the sulfide bleb clusters in large impact melts in shergottites. (9th December 2021) - Rao, M. N.; Nyquist, L. E.; Asimow, P. D.; Ross, D. K.; Sutton, S. R.; See, T. H.; Shih, C. Y.; Garrison, D. H.; Wentworth, S. J.; Park, J.
Abstract: Large impact‐melt pockets in shergottites contain both Martian regolith components and sulfide/sulfite bleb clusters that yield high sulfur concentrations locally compared to bulk shergottites. The regolith may be the source of excess sulfur in the shergottite melt pockets. To explore whether shock and release of secondary Fe‐sulfates trapped in host rock voids is a plausible mechanism to generate the shergottite sulfur bleb clusters, we carried out shock recovery experiments on an analog mixture of ferric sulfate and Columbia River basalt at peak pressures of 21 and 31 GPa. The recovered products from the 31 GPa experiment show mixtures of Fe‐sulfide and Fe‐sulfite blebs similar to the sulfur‐rich bleb clusters found in shergottite impact melts. The 21 GPa experiment did not yield such blebs. The collapse of porosity and local high‐strain shear heating in the 31 GPa experiment presumably created high‐temperature hotspots (~2000 °C) sufficient to reduce Fe 3+ to Fe 2+ and to decompose sulfate to sulfite, followed by concomitant reduction to sulfide during pressure release. Our results suggest that similar processes might have transpired during shock production of sulfur‐rich bleb clusters in shergottite impact melts. It is possible that very small CO presence in our experiments could have catalyzed the reduction process. We plan to repeat the experiments without CO.